PENGARUH MODEL STUDENT FACILITATOR AND EXPLAINING (SFAE) TERHADAP KEMAMPUAN BERBICARA PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SD NEGERI 88 PALEMBANG - Enjelia Berliana Maharani; M.Taheri Akhbar; Mega Prasrihamni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine and describe whether or not there is a significant effect of the Student Facilitator And Explaining learning model on students' speaking skills in grade V Indonesian language learning at SD Negeri 88 Palembang. The research method used in this study is the experimental method of the Pretest-Posttest Control Group Design model by dividing the sample into two groups, namely the experimental group and the control group. The experimental group was class V.1 students and the control group was class V.2 students. The data collection technique used in this study is in the form of tests, the tests used in this study are the initial test and the final test in the form of an assessment component in speaking ability which assesses 5 aspects of assessment. The results of this study showed that the pretest (initial test) in the experimental class had an average of 62.45 with a sufficient category, after being given treatment using the SFAE model the results of the final test (posttest) in the experimental class showed a value of 80.00 with a good category. This shows that. obtained sig value (2-tailed) 0.000 <0.05. Thus it can be said that Ho is rejected and Ha is accepted, meaning that there is a significant effect of the Student Facilitator And Explaining learning model on student speaking skills in grade V Indonesian language learning at SD Negeri 88 Palembang.